Pengaruh metode latihan kardio dan tabata dalam mengurangi lemak tubuh dan meningkatkan kapasitas aerobik maksimum pada siswa obesitas - Muhammad, Muhammad; Rusdiawan, Afif; Irsyada, Machfud; Subagio, Irmantara; Wismanadi, Himawan (Universitas Nusantara PGRI Kediri, 2023)
This study aimed to determine the effect of cardio and tabata training on reducing body fat and increasing aerobic capacity. This research is an experimental research with a pre and post-control group design. The research sample was split into three groups, each with 9 participants: control group (K1), cardio group (K2), and Tabata group (K3), group division was carried out randomly on research subjects. K1 without any exercise, whereas K2 (cardio) is running and skipping at an intensity of 55% and 70% of one's maximum heart rate. K3 (Tabata) performs burpees and jogging with a 90% – 95% HR maximum intensity. A skinfold calliper was used to quantify body fat, and a 12-minute Cooper test was used to gauge aerobic capacity. The Manova test was employed for data analysis, and a significance threshold 0.05 was used. The result of this study is that K3 had significantly less body fat than K1 and K2, and K2 had significantly less body fat than K1 (p 0.05). Comparing K3 and K2 to K1, aerobic capacity was substantially improved (p 0.05). In conclusion, six weeks of cardio and Tabata training impacted lowering body fat and raising maximum aerobic capacity.